how do you solve a quadratic formula and end up with a square root? please be specific and show steps
Thank you for the opportunity to help you with your question!
First notice the quadratic formula is
x = -b +/- sqrt(b^2 - 4ac) / 2a
Notice the square root in the formula?
Let's say we have the function y = x^2 - 3
In this case a = 1, b = 0, and c = -3
Plugging into the formula
x = -(0) +/-sqrt(0 - 4(1)(-3)) / 2(1)
= +/-sqrt(12) / 2
= +/-2sqrt(3) / 2
Content will be erased after question is completed.
Enter the email address associated with your account, and we will email you a link to reset your password.
Forgot your password?